Caste and class ideology in contemporary India - Kumar, Vikramendra (New Delhi Rawat publication, 2025)
Caste and Class Ideology in Contemporary India begins with an overview of major theoretical considerations of caste to elaborate on the genesis, mechanism and the function of the caste system in India. It critically examines the persistence of caste in modern Indian society, challenging the notion that caste is an archaic system compensated for by affirmative action. The book argues that caste continues to function as both a source of discrimination and a structure of advantage, especially in the post-liberalization economy.
Keywords: Caste and politics in India; Caste in modern India; Discourse on caste system